KETEPATAN PEMERIKSAAN RADIOLOGI DAN BTA APUSAN LANGSUNG DENGAN KULTUR DALAM DIAGNOSIS TUBERKULOSIS PARU DI MEDAN - S*, Erfiyani; Tarigan**, Amira Permatasari (Politeknik Kesehatan Kemetrian Kesehatan Medan, 2015)
Lung tuberculosis is one of transmitted diseases which are caused by Mycobacterium tuberculosis throughnuclei droplet. Diagnosis for lung tuberculosis is usually detected by the examination of direct sputumremoval, thorax photo, and Culture. The type of the research was descriptive study by using diagnostic testand the samples consisted of sputum and thorax photo. The sputum was taken accidentally, in the morning,and accidentally which was examined by using Ziehl Nelsen method and culture. The objective of theresearch was to find out the effectiveness of examining direct BTA removal and radiology which werecompared with Culture. The samples were taken from Private Practice of Tuberculosis Specialists in Medanand in BP4, Medan which had fulfilled inclusive criteria, radiology examination and three times of phlegmtaking for direct BTA removal and culture were performed; after that, radiology diagnostic test for directBTA removal was compared with Culture. 60 samples on direct removal method indicated the value ofsensitivity of 59.38%, specificity of 92.86%, value of positive prediction of 90.48%, value of negativeprediction of 66.7%, ratio of positive likelihood of 8.31, and ratio of negative likelihood of 0.44. Radiologymethod indicated sensitivity of 62.63%, specificity of 82.14%, the value of positive prediction of 80.77%,value of negative prediction of 67.65%, ratio of positive likelihood of 3.67, and ratio of negative likelihood of0.42. Of the 21 samples, positive BTA which underwent minimum lung damage of 4 (6.7%), moderatedamage of 9 (15.0%), and wide damage of 5 (8.3%). The result of the research showed that radiologyexamination indicated that the value of sensitivity was higher than direct removal method, compared withculture as gold standard in BTA examination.That clinical benefit was bigger in direct removal method canbe seen from the value of positive prediction which was higher than radiology method so that it isrecommended that both examination techniques be used to diagnose lung tuberculosis